Performance of the global minimum variance portfolio : a study on correlation and volatility estimation. - Tan, Wei Hao. (2012)
This paper studies the returns of efficient portfolios based on different estimations of the covariance matrix. More specifically we derive the Global Minimum Variance Portfolio (GMVP) weights, using different estimation methodologies to derive